Effects of maltitol and carboxymethylcellulose pre-treatments on the physicochemical properties and acceptability of fried potato crisps / Bazilah Mat Saud - Mat Saud, Bazilah (Faculty of Applied Sciences, 2013)
The objectives of this study were to determine the effect of using different concentration of maltitol (10% and 23%) and CMC (2% and 3%) on the oil content of potato crisps, and to determine the changes in the physicochemical properties in terms of moisture content, water activity, colour, texture and acceptability of potato crisps. The potatoes were peeled, sliced, blanched, dried, dipped in maltitol and CMC solution for 10s prior to deep frying. Dipping of potato in different concentration of maltitol and CMC significantly reduced the oil uptake up to 25%. The raw potato treated with 3% CMC had significantly higher (p<0.05) moisture content compared to control and sample treated with maltitol. Fried potato crisps treated in 3% CMC also had significantly higher moisture content (p<0.05) compared to other samples. Potato dipped in 10% maltitol had significantly different (p<0.05) with the control and potato dipped in 3% CMC in term of water activity. Potato crisps dipped in 3% CMC had significantly the highest (p<0.05) crispiness compared to other samples. Dipping of potato in different concentration of maltitol had no significant effect (p>0.05) on the crispiness. No significant effect (p>0.05) on the redness (a*) and yellowness (b*) value of the potato crisps except for lightness (L*) value. Potato dipped in 2% CMC had significantly lowest in lightness (L*) value compare to other samples indicating it was darker in colour. Sensory result indicated that there were no significant different (p>0.05) in appearance, colour and taste but there were significant different in oiliness, crispiness and overall acceptability. Potato crisps treated with 3% CMC had higher score in oiliness compared to control and potato dipped in 23% maltitol. This score gave by the panelists due to the less oiliness in potato crisps. Potato dipped in maltitol was most acceptable in term of crispiness. For overall acceptability, potato treated with 23% maltitol was more acceptable than control sample and sample treated with 2% CMC.